Factors associated with false‐negative cardiovascular magnetic resonance perfusion studies: A Clinical evaluation of magnetic resonance imaging in coronary artery disease (CE‐MARC) substudy. Issue 3 (18th August 2015) - Kidambi, Ananth; Sourbron, Steven; Maredia, Neil; Motwani, Manish; Brown, Julia M.; Nixon, Jane; Everett, Colin C.; Plein, Sven; Greenwood, John P.
Abstract : Purpose: To examine factors associated with false‐negative cardiovascular magnetic resonance (MR) perfusion studies within the large prospective Clinical Evaluation of MR imaging in Coronary artery disease (CE‐MARC) study population. Myocardial perfusion MR has excellent diagnostic accuracy to detect coronary heart disease (CHD). However, causes of false‐negative MR perfusion studies are not well understood. Materials and Methods: CE‐MARC prospectively recruited patients with suspected CHD and mandated MR, myocardial perfusion scintigraphy, and invasive angiography. This subanalysis identified all patients with significant coronary stenosis by quantitative coronary angiography (QCA) and MR perfusion (1.5T, T 1 ‐weighted gradient echo), using the original blinded image read. We explored patient and imaging characteristics related to false‐negative or true‐positive MR perfusion results, with reference to QCA. Multivariate regression analysis assessed the likelihood of false‐negative MR perfusion according to four characteristics: poor image quality, triple‐vessel disease, inadequate hemodynamic response to adenosine, and Duke jeopardy score (angiographic myocardium‐at‐risk score). Results: In all, 265 (39%) patients had significant angiographic disease (mean age 62, 79% male). Thirty‐five (5%) had false‐negative and 230 (34%) true‐positive MR perfusion. Poor MR perfusion image quality, triple‐vessel disease, and inadequate hemodynamic response were similar between false‐negative and true‐positive groups (odds ratio, OR [95% confidence interval, CI]: 4.1 (0.82–21.0), P  = 0.09; 1.2 (0.20–7.1), P  = 0.85, and 1.6 (0.65–3.8), P  = 0.31, respectively). Mean Duke jeopardy score was significantly lower in the false‐negative group (2.6 ± 1.7 vs. 5.4 ± 3.0, OR 0.34 (0.21–0.53), P  < 0.0001). Conclusion: False‐negative cardiovascular MR perfusion studies are uncommon, and more common in patients with lower angiographic myocardium‐at‐risk. In CE‐MARC, poor image quality, triple‐vessel disease, and inadequate hemodynamic response were not significantly associated with false‐negative MR perfusion. J. MAGN. RESON. IMAGING 2016;43:566–573.